(3bhi GdCZPjI hGdCOhjIs
(3ChdgG (B:s
(3GdMdh MGQ , EdG Cfg djS TOjO GdMQGQI , hdG jXgQ efg ESNGf bhi , EdG Cf jOef Ch jchf GdBcd eJgjFkG dPdc s
(3BNQgG (B:s
(3Ch jWHN HGdRjJ , aEfg EPG WHN eY GdRjJ ZGjI ddHQO , hjWdb GdWHjYI ddeHQhOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdebGdI GdKGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B186 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdRGhjI GdMeRGhjI (B(1/127) s
Keywords: (3GdWHs